Prescribed signal concentration on the boundary: eventual smoothness in a chemotaxis-Navier–Stokes system with logistic proliferation - Black, Tobias; Wu, Chunyan (Calculus of Variations and Partial Differential Equations)
Keywords: Applied Mathematics; Analysis

Rapid preparation of self-supported nickel–iron oxide as a high-performance glucose sensing platform - Ni, Ming; Tan, Minyuan; Pan, Ying; Zhu, Chuhong; Du, Haiwei (Journal of Materials Chemistry C)
Nickel–iron oxide electrocatalysts prepared via a rapid electrodeposition are promising candidates for non-enzymatic glucose sensors.
Keywords: Materials Chemistry; General Chemistry

Experimental investigation of organic Rankine cycle performance using alkanes or hexamethyldisiloxane as a working fluid - Abbas, Wameedh Khider Abbas; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Experimental investigation of organic Rankine cycle performance using alkanes or hexamethyldisiloxane as a working fluid - Abbas, Wameedh Khider Abbas; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Anne-Christine Brehm, Netzwerk Gotik. Das Ulmer Münster im Zentrum von Architektur- und Bautechniktransfer - Harnack, Maria (Blätter für württembergische Kirchengeschichte)

Im-materiell. Kulturerbe-Studien für Eva-Maria Seng zum 60. Geburtstag

Motorische Kompetenzen im Kindesalter: Monitoring, Intervention und Zusammenhänge mit der Selbstwahrnehmung - Strotmeyer, Anne
Motorische Kompetenzen und die Selbstwahrnehmung dieser sind zentral hinsichtlich der Ausbildung eines gesundheitsförderlichen Lebensstils. Bewegungsmangel im Kindesalter und motorische Defizite unterstreichen die Relevanz von Untersuchungen in diesem Forschungsfeld. In diesem Kontext besteht Forschungsbedarf, welcher an der jungen Forschungslinie zu motorischen Basiskompetenzen ansetzt. Daher zielt die vorliegende Arbeit auf die Untersuchung motorischer Basiskompetenzen im Kontext des Monitorings, der Intervention sowie der Untersuchung von Zusammenhängen mit der Selbstwahrnehmung. Es wurden konfirmatorische Faktorenanalysen durchgeführt sowie eine kompetenzorientierte Intervention für das mittlere Kindesalter konzipiert und evaluiert. Zudem fanden Varianzanalysen mit Messwiederholung und manifeste Pfadmodelle Anwendung. Neben der Bestätigung der faktoriellen Struktur des Tests zur Erfassung motorischer Basiskompetenzen (MOBAK 3-4), wurden Zusammenhänge mit endogenen sowie exogenen Faktoren nachgewiesen. Es konnte gezeigt werden, dass mit Hilfe der relativ kurzen Intervention positive Effekte auf die motorischen Basiskompetenzen erzielt werden können. Zudem zeigten sich moderate Korrelationen zwischen motorischen Basiskompetenzen und der Selbstwahrnehmung. Auf Grundlage dieser Befunde sollten im Bereich der Objektkontrolle vor allem motorische Kompetenzen und im Bereich der Lokomotion insbesondere die Selbstwahrnehmung zur Steigerung des Kompetenzlevels gefördert werden.

Lernerkorpora als Ressource in der quantitativen DaF-Forschung - Weber, Tassja (Vermitteln – Verbinden – Verstehen)

Lattice QCD noise reduction for bosonic correlators through blocking - Altenkort, Luis; Eller, Alexander M.; Kaczmarek, O.; Mazur, Lukas; Moore, Guy D.; Shu, Hai-Tao (Physical Review D)

Wundersame Materie. Neomaterialistische Perspektiven auf Relationalität, Wirkmacht und Sprache - Kostan, Anastassija; Hoppe, Katharina (Die Kraft des Staunens: der neue Materialismus in der Gegenwartskunst)

Die Sprache der Materie: Feministische Neomaterialismen zwischen diskursiver Intelligibilität und posthumanistischer Performativität - Kostan, Anastassija (Sociality-Materiality-Practice. Sozialität-Materialität-Praxis)

Woundrous Matter. New Materialist Perspectives on Relationalism, Agency, and Language - Kostan, Anastassija; Hoppe, Katharina (The Power of Wonder. New Materialisms in Contemporary Art)

Feministische Neomaterialismen. Die relationale Immanenz posthumanen Handelns - Kostan, Anastassija

About the structure of the discrete and continuous Eringen’s nonlocal elastica - Cresson, Jacky; Hariz-Belgacem, Khaled (Mathematics and Mechanics of Solids)
The Eringen’s nonlocal elastica equation does not possess a Lagrangian formulation. In this article, we find a variational integrating factor which enables us to provide a Lagrangian and Hamiltonian structure associated to this equation. Explicit expressions of the solutions in terms of elliptic integrals of the first kind are then deduced. We then derive discrete version of the Eringen’s nonlocal elastica preserving the Lagrangian and Hamiltonian structure and compare it with Challamel’s and co-worker definition of a discrete Eringen’s nonlocal elastica.
Keywords: Mechanics of Materials; General Materials Science; General Mathematics

Roadmap on Electronic Structure Codes in the Exascale Era - Gavini, Vikram; Baroni, Stefano; Blum, Volker; Bowler, David R.; Buccheri, Alexander; Chelikowsky, James R.; Das, Sambit; Dawson, William; Delugas, Pietro; Dogan, Mehmet; Draxl, Claudia; Galli, Giulia; et al. (arXiv:2209.12747)
Electronic structure calculations have been instrumental in providing many important insights into a range of physical and chemical properties of various molecular and solid-state systems. Their importance to various fields, including materials science, chemical sciences, computational chemistry and device physics, is underscored by the large fraction of available public supercomputing resources devoted to these calculations. As we enter the exascale era, exciting new opportunities to increase simulation numbers, sizes, and accuracies present themselves. In order to realize these promises, the community of electronic structure software developers will however first have to tackle a number of challenges pertaining to the efficient use of new architectures that will rely heavily on massive parallelism and hardware accelerators. This roadmap provides a broad overview of the state-of-the-art in electronic structure calculations and of the various new directions being pursued by the community. It covers 14 electronic structure codes, presenting their current status, their development priorities over the next five years, and their plans towards tackling the challenges and leveraging the opportunities presented by the advent of exascale computing.

A High-Fidelity Flow Solver for Unstructured Meshes on Field-Programmable Gate Arrays: Design, Evaluation, and Future Challenges - Karp, Martin; Podobas, Artur; Kenter, Tobias; Jansson, Niclas; Plessl, Christian; Schlatter, Philipp; Markidis, Stefano (International Conference on High Performance Computing in Asia-Pacific Region)

Hermeneutik zwischen Logik und Ethik - Ficara, Elena (Ethik in der Hermeneutik – Hermeneutik in der Ethik)

About the structure of the discrete and continuous Eringen’s nonlocal elastica - Cresson, Jacky; Hariz Belgacem, Khaled (Mathematics and Mechanics of Solids)
The Eringen’s nonlocal elastica equation does not possess a Lagrangian formulation. In this article, we find a variational integrating factor which enables us to provide a Lagrangian and Hamiltonian structure associated to this equation. Explicit expressions of the solutions in terms of elliptic integrals of the first kind are then deduced. We then derive discrete version of the Eringen’s nonlocal elastica preserving the Lagrangian and Hamiltonian structure and compare it with Challamel’s and co-worker definition of a discrete Eringen’s nonlocal elastica.
Keywords: Mechanics of Materials; General Materials Science; General Mathematics

CP2K on the road to exascale - Kühne, Thomas; Plessl, Christian; Schade, Robert; Schütt, Ole (arXiv:2205.14741)
The CP2K program package, which can be considered as the swiss army knife of atomistic simulations, is presented with a special emphasis on ab-initio molecular dynamics using the second-generation Car-Parrinello method. After outlining current and near-term development efforts with regards to massively parallel low-scaling post-Hartree-Fock and eigenvalue solvers, novel approaches on how we plan to take full advantage of future low-precision hardware architectures are introduced. Our focus here is on combining our submatrix method with the approximate computing paradigm to address the immanent exascale era.

Parallel quantum chemistry on noisy intermediate-scale quantum computers - Schade, Robert; Bauer, Carsten; Tamoev, Konstantin; Mazur, Lukas; Plessl, Christian; Kühne, Thomas (Phys. Rev. Research)
A parallel hybrid quantum-classical algorithm for the solution of the quantum-chemical ground-state energy problem on gate-based quantum computers is presented. This approach is based on the reduced density-matrix functional theory (RDMFT) formulation of the electronic structure problem. For that purpose, the density-matrix functional of the full system is decomposed into an indirectly coupled sum of density-matrix functionals for all its subsystems using the adaptive cluster approximation to RDMFT. The approximations involved in the decomposition and the adaptive cluster approximation itself can be systematically converged to the exact result. The solutions for the density-matrix functionals of the effective subsystems involves a constrained minimization over many-particle states that are approximated by parametrized trial states on the quantum computer similarly to the variational quantum eigensolver. The independence of the density-matrix functionals of the effective subsystems introduces a new level of parallelization and allows for the computational treatment of much larger molecules on a quantum computer with a given qubit count. In addition, for the proposed algorithm techniques are presented to reduce the qubit count, the number of quantum programs, as well as its depth. The evaluation of a density-matrix functional as the essential part of our approach is demonstrated for Hubbard-like systems on IBM quantum computers based on superconducting transmon qubits.